Qualitative Study on Pregnant Women's Perceptions of Iron Tablet Administration in Anemia Prevention during the First to Third Trimesters - Yahya, Fajar Dhini; Munawwarah, St.; Hasriantirisna, Hasriantirisna; Nanda, Kiki Riskianti (Advances in Healthcare Research, 2025)
Purpose: This study aims to evaluate the effect of iron tablet supplementation on pregnant women from the first to the third trimester in preventing pregnancy-related anemia. The primary focus is on understanding the dynamics of consumption compliance, maternal perceptions, the effectiveness of health education, as well as environmental factors and accessibility that influence the success of the intervention. Research Method: This study employed a qualitative approach, based on a systematic literature review of relevant publications from 2018 to 2025. The analysis was conducted thematically to identify consumption patterns, motivations, educational interventions, and their impact on the hemoglobin status of pregnant women. Results and Discussion: The findings indicate a progressive trend in adherence to iron tablet consumption from the first to the third trimester, with the main barriers being complaints of nausea and gastrointestinal side effects. Positive perceptions of the benefits of iron tablets, along with appropriate social support and education, have been shown to improve adherence. Health education tailored to the stage of pregnancy is more effective in changing behavior. Consistent iron tablet consumption contributes to increased hemoglobin levels and reduces the risk of anemia, as well as pregnancy complications such as preterm birth and low birth weight. Implications: This study provides original contributions to the development of trimester-based maternal health education strategies and the improvement of iron tablet availability in primary care. The implications include strengthening maternal and child health program policies and involving multiple stakeholders, including families and communities, in supporting the success of interventions.